Legume Plant Growth at Various Levels of Drought Stress Treatment - Veronica Sinamo; Nevy Diana Hanafi; Tri Hesty Wahyuni (Indonesian Journal of Agricultural Research, 2018)
A strategic alternative step for the development of cultivation of feed crops is to optimize the use of dry land that has the potential for agricultural and livestock business. One of the forage plants that has good adaptation to less good soil condition and is a pioneer plant, Pueraria javanica legume, so it can be considered as a potential alternative forage as animal feed. The research aims at determining the effect of various levels of drought stress treatment on the plant hight, fresh matter production, dry matter production and root biomass of Pueraria javanica legume. The experiment was conducted in the Greenhouse of the Agriculture Faculty of Universitas Sumatera Utara. The experiment was carried out using a completely randomized design (CRD) with 3 treatments and 4 replications. The treatments were A1 (25% field capacity (FC)=144 ml/polybag, A2 (50% FC)=288 ml/polybag and A3 (100% FC)=576 ml/polybag. The results show that Pueraria javanica legume can survive and grow up to severe drought stress (25% FC) but the crop production does not increase when compared to the field capacity condition; besides, the legume cannot survive longer in drought condition. The volume of water supplied corresponding to the field capacity makes the plant growth better.